Spain and the Abolition of Slavery in Cuba, 1817-1886 - Corwin, Arthur F. (Dallas : Published for the Institute of Latin American Studies, 1967)
How African Slaves Were First Brought to the Antilles. A United Front in Cuba. Abolitionism Invades Spanis. Application of the Moret Law and Abolition in Puerto Rico, 1872-1873.